SAVING ELECTRICAL ENERGY BY AUTOMATIZING THE OPERATING MODE OF THE ELECTRIC DRIVE OF THE SHAFT GAS SUPPORTING VENTILATION DEVICE (Web of Teachers: Inderscience Research, 2025)
The article analyzes measures aimed at effective automation of the electric drive in the operating mode of mine ventilation fans. For this purpose, we are talking about the methods of operation of mine fans, the introduction of innovative equipment and automation systems for saving electricity and increasing energy efficiency. The article examines the importance of modernizing the electric drive, creating control and automatic control systems in mine conditions, as well as strengthening automation to ensure safety. At the same time, information will also be provided on the registration of fan operation, operating in optimal mode, and methods of effective control of air flows through fans. The article emphasizes the importance of promoting modern directions and practices for increasing the ecological and energy efficiency of mine production.